BINGKAI MODERASI BERAGAMA PADA YOUTUBE MUI LAMPUNG - Umi Rojiati; Ocha Nasria Putri; Nandang Kusnandar; Evy Septiana Rachman (INSTITUT AGAMA ISLAM NEGERI METRO, 2022)
Indonesia is known as a nation that upholds the values of tolerance in terms of religious diversity. The values that exist in religion are maintained, combined and united with the values of local customs and wisdom so that the implementation of religious and cultural rituals runs peacefully and harmoniously. However, at the practical level, there are still various acts of intolerance that occur. Referring to the existing problems of the Indonesian Ulema Council (MUI), especially Lampung Province, as a unifying forum for people to continue to carry out proselytizing activities, especially regarding Religious Moderation by following the times through the official youtube channel of MUI Lampung. This research is included in the type of library research which can be interpreted as finding research sources derived from books related to the frame of religious moderation on MUI Youtube buoy ( vandjick discourse analysis). This research is also a qualitative research method. The research referred to here is related to the ability of researchers to interpret the data obtained. There are two common (thematic) themes in the discourse. First, build tolerance in society in the midst of diversity. The tolerance emphasized here is about religious tolerance. Second, there are acts of intolerance that occur in society. In terms of social cognition, MUI Lampung provides an understanding to the community of the importance of tolerance. while in the social consequences seen from the shops and access, MUI Lampung succeeded in influencing the audience.